Pengembangan Bibliokonseling untuk Meningkatkan Motivasi Belajar Siswa - Sari, Eva Kartika Wulan (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
Students experience learning motivation problems that come from internal factors, namely feeling lazy to study. The right technique to increase learning motivation is Bibliocounseling because it is a form of therapeutic support through reading materials to help students who have problems. Development was carried out using the ADDIE model. Through four research instruments, namely, a needs questionnaire, an interview guide, a learning motivation scale, and an assessment format for Bibliocounseling books. There are three stages in assessing the validity and reliability of Bibliocounseling, namely testing the validity and reliability of counseling material experts, media, and language. Quantitative and qualitative data were obtained, then processed, then used as a basis for continuing the development of Bibliocounseling values. The validity and reliability assessment shows that the product is made is valid and reliable because it meets the aspects of usability, attractiveness, convenience, and accuracy so it is hoped that it can increase student learning motivation.